Controlled joule-heating of suspended glassy carbon wires for localized chemical vapor deposition. (January 2020) - Cisquella-Serra, Albert; Gamero-Castaño, Manuel; Ferrer-Argemi, Laia; Wardini, Jenna; Madou, Marc
Abstract: This paper demonstrates for the first time localized chemical vapor deposition of WO3-x on a suspended glassy carbon wire. A process based on the photopatterning of an SU-8 scaffold, the near-field electrospinning of an SU-8 fiber, and their pyrolysis yields a monolithic carbon structure featuring a glassy carbon wire of known diameter and length, suspended on a glassy carbon scaffold. The temperature required for the deposition of WO3-x is generated by passing current through the wire, which causes Joule heating. The deposition starts in the midpoint of the wire, and extends to its ends as the current is increased. The thickness and length of the coating are functions of the imposed current. The evolution of the coating can be monitored in real time by measuring the voltage vs current characteristic of the wire. We have deposited WO3-x coatings with thickness from 71 nm to 1.4 μm, in glassy carbon wires with diameters between 780 nm and 2.95 μm. The coatings are uniform and polycrystalline. The suspended glassy carbon wire is a generic platform for the deposition of many transition metal oxide (TMO) coatings, and opens the door to carbon-TMO structures for applications including catalysis and gas sensing. Graphical abstract: Image 1